Paradoxes of experiencing of space by persons with anorexia - Starzomska, Małgorzata (Studia Psychologica: Theoria et praxis, 2007)
Anorexia is a grave and disabling mental disorder. The article describes spatial experiences among anorexics within the framework of existential-phenomenological theory. The analysis of anorexics’ experiences which was presented in the article, focuses especially on: “nature world” and “ideal world” and points to specific, paradoxical hierarchy and meanings of these worlds for people who suffer from anorexia. The most useful therapeutic option for such patients can be showing them, that except starving, there are probably other methods of “core self” protection and self-realization.